Health Literacy in Occupational Therapy Research: A Scoping Review - Erin Attard; Andraya Musallam; Kirsten Vaas; Taylar Chaney; Jennifer Fortuna; Betsy Williams (Scholarworks @ WMU, 2021)
Background: Low health literacy is a significant problem in the United States. Patient education is a key component of occupational therapy intervention. Occupational therapists have the skills to develop patient education materials (PEMs) all patients can understand. Few studies on health literacy exist in occupational therapy research. The purpose of this scoping review was to summarize the breadth of literature on health literacy in occupational therapy research and to identify knowledge gaps. Method: A scoping review methodological framework (Arksey and O'Malley, 2005; Levac et al., 2010) was used to search five databases. A descriptive numerical summary and qualitative thematic analysis were used to summarize the results. Results: Eighteen articles met the inclusion criteria. Quantitative results describe variation in research design, outcome measures, intervention focus, and setting. Qualitative themes include exploring health literacy knowledge, practices and perceptions of occupational therapists, and assessment of consumer needs and understanding related to health literacy. Gaps in the literature include the impact of low health literacy on patient outcomes, guidelines for appraising and modifying PEMs, and the effectiveness of modified PEMs. Conclusion: There is a need to establish evidence-based guidelines and a standard of care for patients with low health literacy.